Moderating Influence of Gender Dynamics on Conservation Agricultural Project Practices and Food Security Among Smallholder Farmers in Solai, Nakuru County - Githendu, Stephen Mwai (Kabarak University, 2025)
Abstract Conservation agriculture project practices have been promoted as one of the few technologies affordable to farmers, aiming to improve yields while conserving the environment. Despite the known benefits of Conservation Agriculture, Solai in Subukia sub-County still faces food insecurity, with low adoption among smallholder farmers. This study examined how gender dynamics influenced the relationship between conservation agriculture practices and food security, focusing on cropping methods, minimum soil tillage, continuous soil cover, and the moderating role of gender. The study adopted a cross-sectional survey design and involved smallholder farmers actively participating in conservation agriculture initiatives. This study adopts a cross-sectional descriptive survey design and correlational research design to explore the impact of Conservation Agriculture practices on food security among smallholder farmers. The cross-sectional survey provided a snapshot of current agricultural practices and food security indicators at a single point in time, while the correlational design investigated relationships between variables, specifically examining how adoption of Conservation Agriculture practices relates to food security outcomes. The target population included 107 respondents, including 95 smallholder farmers registered under the Anglican Development Services-Central Rift, who have been practicing Conservation Agriculture for the past three years, and the 6 ADS-CR staff members, 2 ward extension officers for Solai and Kabazi, and local administration (chief and 3 assistants) involved in project oversight. This diverse sample ensured comprehensive insights into the impact of CA on food security in the study area. Data collection methods included structured questionnaires administered during household visits and interviews with key stakeholders. Questionnaires employed Likert scales to assess farmers' perceptions of Conservation Agricultural practices, effectiveness in enhancing crop yield and soil health, challenges encountered, and overall contribution to food security. Interviews provided qualitative insights from ADS-CR staff, ward extension officers, and local administration on project implementation and community engagement. Data analysis involved descriptive statistics to summarize quantitative data and inferential techniques such as correlation and regression analysis to examine relationships between Conservation Agricultural practices and food security outcomes. The study aimed to provide empirical evidence to inform policy and practice in sustainable agriculture, contributing to enhanced food security and environmental sustainability in similar agricultural contexts. Descriptive statistics revealed moderate perceptions of these practices, with average means of 2.70 (SD = 1.299) for cropping methods, 2.84 (SD = 1.257) for minimum tillage, 2.52 (SD = 1.20) for soil cover, and 2.56 (SD = 1.210) for gender dynamics. Correlation results showed strong positive links with food security, where cropping methods had r = 0.902, p < 0.01, soil cover r = 0.921, p < 0.01, gender dynamics r = 0.921, p < 0.01, and minimum tillage r = 0.766, p < 0.01. Regression showed cropping methods β = 0.472, p = 0.000, gender dynamics β = 0.375, p = 0.000, soil cover β = 0.372, p = 0.000, and minimum tillage β = 0.196, p = 0.002. Gender dynamics also moderated cropping methods, with β = 0.223 and p = 0.000. The study concluded that these agricultural practices, when combined with gender-inclusive approaches, contribute significantly to sustainable food production and improved food security outcomes. The study recommends promoting these practices across Kenya and suggests further research into the socio-economic barriers hindering their adoption in diverse ecological zones.
Full text
Keywords: Cropping Method; Minimum Soil Tillage; Continuous Soil Cover; Gender Dynamics.